The implementation of Christian family values in charismatic churches in Ukraine (on the example of the church "New Generation") - Tyshchenko, Andriy Georgiоvich (Relihijna svoboda, 2018)
The article deals with the specifics of religion as a regulator of relations in society and family. The analysis of the actualization of Christian family values and the form of their implementation on the example of the Church "New Generation", in the conditions of the revival of religious life and the development of Ukraine as a polyconfessional state is analyzed. Shown is the change in the role of the church and the extent of the impact of Christian values on the social in the regional dimension, as well as those social problems that the church should deal with. It turns out that the crisis of a modern family prompts Christian denominations to react to the existing state of affairs. This forms a confessional specificity in understanding the roots and ways of solving the problems of society. Charismatic churches today are characterized by increasing recognition, increasing tolerance in society, deepening of institutionalizing change, and the formation of their own theology. They function in the Ukrainian society and cause more or less influence on different components of society. Charismatics do not have a single center or doctrine, so the purpose of this article is to clarify the peculiarities of actualization of Christian family values ​​and the specifics of their implementation in the theology and activities of the charismatic Church "The New Generation"). The task of the article is to determine the specifics of theological understanding, the main forms of the practical solution of the charismatic Church "New Generation" of those problems that exist in the Ukrainian society and are related to the family as a primary collective. Another task is to investigate the influence of the church's role on marriage relations and the family in the region. It is stated that the theological basis of the Church "The New Generation" is in the dynamics of formation, based on the general religious principles of Christianity in general and Protestantism in particular. The Christian system of values has a theistic-objectivist character for them. The Protestant principle of "Soli Deo gloria" ("only God's glory") laid the foundation for the formation of the family values of carismatic spirituality carriers. The charismatic church as an institution reacts to constant changes in all spheres of society's life. It becomes mobile, open to change, modernizes, and tests various forms of solving relevant social problems associated with the family. The charismatic church's position on marriage is serious and well-considered. In the ecclesiastical environment, a series of seminars devoted to family and marriage issues have been developed, and preventive and spiritual work is being conducted on the prevention of hasty marriages. The region's statistics indicate positive changes towards strengthening the family's institute, reducing the number of divorces, and so on. Such indicators allow us to speak about the positive influence of the activity of the charismatic Church "The New Generation" on church parishioners, on the situation in the city and the region, as the "New Generation" subsidiary churches are located throughout the region. This testifies to the effectiveness of the practical activities of the charismatic Church "New Generation" in the region and the desire to extend its experience to other regions of Ukraine. The results of the research can be used in religious studies courses, in particular in the teaching of disciplines related to the study of Christian and non-Christian trends, the specifics of new religious movements, as well as for state bodies, with the aim of improving the state-confessional relations and harmonizing social work with the population.